2006
DOI: 10.1080/14616730600785686
|View full text |Cite
|
Sign up to set email alerts
|

Teenage pregnancy, attachment style, and depression: A comparison of teenage and adult pregnant women in a Portuguese series

Abstract: The aim of this Portuguese study is to compare the experience of pregnancy in teenage years and later adulthood and to examine insecure attachment style as a risk factor for depression during pregnancy. The Attachment Style Interview (ASI; Bifulco, Moran, Ball, & Bernazzani, 2002) and the Edinburgh Postnatal Depression Scale (EPDS; Cox, Holden, & Sagovsky, 1987) were administered to 66 pregnant adolescents and 64 adult women. Pregnant teenagers were found to be nearly three times more likely to have an insecur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 38 publications
3
52
1
8
Order By: Relevance
“…The literature has shown that adult pregnant women receive more social support than do pregnant teenagers. 25,26 However, a recently published study examining the effects of social support on Canadian women during and after pregnancy found that teenage mothers received more social support from the family during pregnancy than adult mothers. 27 The authors argue that because teenagers present more difficulties to connect with their peers, the family may end up providing more support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has shown that adult pregnant women receive more social support than do pregnant teenagers. 25,26 However, a recently published study examining the effects of social support on Canadian women during and after pregnancy found that teenage mothers received more social support from the family during pregnancy than adult mothers. 27 The authors argue that because teenagers present more difficulties to connect with their peers, the family may end up providing more support.…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies show that the absence or lack of support from a companion was more frequent among single teenage mothers or those who did not live with a partner. 25,26 In the United States, a study with pregnant women found that married women had more support than those unmarried and that partner support and marital stability are important factors for health and well-being. 33 Partner support is an important protective factor throughout pregnancy and conception and our study corroborates these findings.…”
Section: Discussionmentioning
confidence: 99%
“…además, bajos puntajes en seguridad del apego implican un mayor riesgo para la depresión posparto. en la misma línea, Figueiredo et al (2006) compararon la experiencia de embarazo en adolescentes y adultas; uno de los principales predictores de la depresión fue el estilo de apego enredado (Bifulco et al, 2002), caracterizado por un elevado deseo de compañía, baja autoconfianza y elevado miedo de separación.…”
Section: Apego Y Depresiónunclassified
“…Aumento da probabilidade do início precoce da atividade sexual e de gravidez na adolescência 103,104 ;…”
Section: Considerações Finaisunclassified